2017
DOI: 10.1002/14651858.cd008996.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone for hypertension

Abstract: Analysis 2.2. Comparison 2 Eplerenone direct dose comparisons, Outcome 2 Diastolic dose response..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 73 publications
1
18
0
4
Order By: Relevance
“…EPL had no significant effects on blood pressure levels. Our observation is consistent with the recent meta-analysis which shows EPL at a dose of 25 mg/day did not produce a statistically significant reduction in systolic or diastolic blood pressure 18 . Our data indicated that MRA maintain eGFR independently of its effects on blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…EPL had no significant effects on blood pressure levels. Our observation is consistent with the recent meta-analysis which shows EPL at a dose of 25 mg/day did not produce a statistically significant reduction in systolic or diastolic blood pressure 18 . Our data indicated that MRA maintain eGFR independently of its effects on blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…This is of major significance because hyperaldosteronism is associated with a plethora of cardiovascular comorbidities and is hallmarked by electrolyte dysregulation [ 9 ]. Moreover, drugs that target aldosterone and its mineralocorticoid receptor, such as spironolactone and eplerenone, are increasingly being used in the management of various pathologies, including hypertension, heart failure, arrhythmias and renal disease [ 10 , 11 ]. Therefore, it is critically important that the ion regulatory pathways of aldosterone are fully understood to understand the unintended consequences of aldosterone-related treatments.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to those seen in study-level pooled analyses including dosages of eplerenone from 50 to 400 mg daily. 27 , 28 Our descriptive secondary endpoint indicated that the percentage of patients controlled to the target BP of 140/90 was numerically greater with eplerenone than with placebo or active comparators. In the placebo-controlled studies, approximately 30% of patients were below target while on placebo, which is a common observation particularly in short-term studies.…”
Section: Discussionmentioning
confidence: 87%